Analysis of Y chromosomal STRs in South of Portugal population with PowerPlex® Y23. (December 2015) - Cruz, M.; Ribeiro, T.; Porto, M.J.; Costa Santos, J.; Carvalho, M.
Abstract: Short tandem repeats (STRs) became a vital tool in forensic genetics due to its high level of polymorphism and abundance in the human genome. Y-chromosome short tandem repeats (Y-STRs) specifically, play an important role in sexual assault cases, where the female component is in greater proportion than the male component, in complex paternity testing of male children and in the process of identification in cases of missing persons or disaster victim identification, involving profiles of male relatives. The PowerPlex ® Y23 System is a five-dye Y-STR multiplex that allows simultaneous genotyping of 23 Y-STR loci (DYS576, DYS389I, DYS448, DYS389II, DYS19, DYS391, DYS481, DYS549, DYS533, DYS438, DYS437, DYS570, DYS635, DYS390, DYS439, DYS392, DYS643, DYS393, DYS458, DYS385a/b, DYS456 and Y-GATA-H4). In this study, samples of 243 unrelated male individuals living in the south of Portugal were amplified in a GeneAmp ® 9700 Thermal Cycler. PCR products were separated and detected on an ABI PRISM ® 3130 xl and the electrophoresis results analyzed with GeneMapper ® ID software v1.2. Allele frequencies and haplotype frequencies were estimated and compared with frequencies from other European population. The results show that the study of Y-STRs using PowerPlex ® Y23 kit, provide a powerful discrimination tool for routine forensic applications.